Critical Discourse Analysis: Hegemony of the Social Media Twitter About National Issues in Indonesia and its Implications to the Discourse Analysis Subject in Colleges - Elvi Susanti (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
Abstract This research is linked with Twitter, as one of social media services on the Internet that are extremely popular in the world, including in Indonesia. This research is important because Twitter is effective in quickly and accurately delivering messages. In fact, everyone can act as a 'reporter' and form quick opinions through this social media. This research is aimed to investigate the emergence of the roots of hegemony based on text analysis that is linked with representation, relation, identity, and transformation of national issues that become trending topics on Twitter. Moreover, the research is to discuss the social media's discourse practice that influences media workers in producing news, and to see how it implicates the research on the study of discourse analysis. By using the Fairclough theory, especially on text analysis that is linked with representation, relation, and identity, the researcher attempts to explore how the roots of hegemony emerge in the national issues that become trending topics on Twitter. The researcher also offers a new function to complete the approach of Fairclough in text analysis on social media: transformation – which is an attempt to see the change in roles of news participants and amateur readers as 'reporters' and participate in forming opinions. Abstrak Penelitian ini berhubungan dengan twitter, sebagai salah satu media sosial di internet yang sangat populer di dunia, termasuk di indonesia. Penelitian ini penting karena twitter efektif dalam menyampaikan pesan dengan cepat dan akurat. Faktanya, semua orang dapat bertindak sebagai